MANAGEMENT OF RECREATIONAL SERVICES IN UKRAINE DURING WARTIME: THE ROLE OF STATE POLICY AND BEST PRACTICES FROM EUROPE - Karyy , O. I.; Bondarenko , Yu. H.; Kulyniak , I. Ya.; Ohinok , S. V. (The actual problems of regional economy development, 2025)
In this article, the role of state policy in Ukraine and the experience of European countries in managing recreational services during wartime are investigated. The purpose of the study is defined as the analysis of specific features of recreational service management in Ukraine under martial law, the identification of the role of public policy in ensuring the comprehensive rehabilitation of individuals affected by the war, and the exploration of the potential for adapting European practices to develop practical management approaches. A comprehensive interdisciplinary methodology is applied, literature and regulatory frameworks are analyzed, a comparative approach is adopted, a systems perspective is employed, and a descriptive-analytical method is utilized to examine recreational service management in wartime Ukraine. The medical-biological, socio-cultural, and economic functions of recreational activities are assessed as essential stages in developing rehabilitation and social adaptation plans for individuals affected by the conflict. The role of public policy in facilitating physical, psychological, and social recovery, adaptation, and reintegration through the development of recreational services is substantiated. The need for improvements in the national recovery system is emphasized, particularly regarding integrated approaches, personalized support, and interagency coordination. Special attention is given to recreation as a critical but underdeveloped component of state policy for comprehensive recovery. A comparative analysis of the implementation of recreational functions in Ukraine and the EU is conducted. Recommendations are proposed to ensure comprehensive rehabilitation of individuals affected by the war, including the creation of conditions for health improvement, rest, and recovery; the implementation of effective psychological support programs; and the development and execution of state programs to support war-affected populations. The findings of this study are expected to be of practical value for public authorities, local governments, and professionals in the fields of tourism and recreation in developing strategies for managing recreational services during wartime and throughout the post-war recovery period.